Financial Hardship and its Associations with Perceived Sleep Quality in Participants with Type 2 Diabetes and Obstructive Sleep Apnea. (March 2023) - Morris, Jonna L.; Belcher, Sarah M.; Jeon, Bomin; Godzik, Cassandra M.; Imes, Christopher C.; Luyster, Faith; Sereika, Susan M.; Scott, Paul W.; Chasens, Eileen R.
Objectives: The purpose of this study was to explore social determinants of health (SDoH), and disease severity as predictors of sleep quality in persons with both Obstructive Sleep Apnea (OSA) and type 2 diabetes (T2D). Methods: Disease severity was measured by Apnea-Hypopnea Index [(AHI) ≥ 5] and HbA1c for glycemic control. SDoH included subjective and objective financial hardship, race, sex, marital status, education, and age. Sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI). Results: The sample (N = 209) was middle-aged (57.6 ± 10.0); 66% White and 34% African American; and 54% men and 46% women. Participants carried a high burden of disease (mean AHI = 20.7 ± 18.1, mean HbA1c = 7.9% ± 1.7%). Disease severity was not significantly associated with sleep quality (all p >.05). Worse sleep quality was associated with both worse subjective (b = -1.54, p = .015) and objective (b = 2.58, p <.001) financial hardship. Characteristics significantly associated with both subjective and objective financial hardship included being African American, female, ≤ 2 years post high school, and of younger ages (all p < .01). Discussion: Financial hardship is a more important predictor of sleep quality than disease severity, age, sex, race, marital status, and educational attainment, in patients with OSA and T2D